Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Biocompatible, highly stretchable, and reusable MoS2-based hydrogel for multisensing and bioelectrical signal monitoring - Chunqing Lin; Chunmei Fu; Yanmei Chen; Nan Zheng; Jie Huang; Yujing Nie; Zhanfeng He; Zanru Guo (Chemical Engineering Journal, 2026)

Crosslinking-regulated dual-network carboxymethyl chitosan/gelatin hydrogel for pH-responsive oral curcumin delivery - Yujing Zhong; Ying Yu; Yonggang Peng; Zhongwen Su; Yangfan Mao; Lin Wang; Meihua Xin; Mingchun Li (Carbohydrate Polymers, 2026)

Rosa laevigata Michx. as a fermentation adjunct modulates microbial succession, metabolic profiles, and sensory quality of Traditional Hakka Huangjiu during brewing - Lin Cheng; Xin Feng; Yujing Wang; Yifang Chen; Bing Li; Feiliang Zhong; Xuegang Luo (Food Bioscience, 2026)

Innovative silk protein peptide-modified soy protein isolate-xanthan gum films for food packaging - Meixia Zheng; Shaojie Zhong; Cheng Lin; Jianfu Chen; Yangyang Liu; Kok Bing Tan; Yujing Zhu (Food Chemistry, 2026)

Dual-halide solid electrolyte interphase engineering with MXene enables dense (110)-oriented Li deposition for high-performance Li metal anodes - Zongyu Mao; Shuaihe Zhang; Ye Han; Yujing Xu; Shuxin Xie; Bei Huang; Shuaihong Chen; Xintong Cai; Junyu Lin; Xiao Yu; Shaozhong Zeng; Dongju Fu; et al. (Chemical Engineering Journal, 2026)

Enhanced synergistic adsorption and peroxymonosulfate oxidation via interlayer-confined MgFe layered double hydroxide/porous biochar composite for water decontamination - Hongmin Zhang; Yifei Yang; Sirui Chen; Yujing Lin; Yongtao Lv; Huihui Zhang; Licheng Chen; Lei Wang; Xudong Wang (Chemical Engineering Journal, 2026)

Removal of polypropylene microplastics from water by microalgae Desmodesmus sp.: Influences, kinetics and mechanisms - Qing Xie; Xiaoai Lin; Lang Tan; Longzao Luo; Shuang Luo; Xiaosong Tian; Qing Cheng; Shao Zhang; Yujing Wang (Algal Research, 2026)

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

Antibacterial properties and mechanisms of anti-lipopolysaccharide factor 1 from Procambarus clarkii - Qing Yang; Zhengyan Du; Lin Yang; Yujing Jia; Xinru Wang; Hao Li; Libo Hou; Lei Zhu; Xianghui Kong (Fish & Shellfish Immunology, 2026)

Mild Decade‐Warming Shifts Soil Organic Carbon Composition Without Altering Total Stock in Temperate and Subtropical Forests - Yujing Yang; Hui Wang; Shirong Liu; Jianming Xue; Peter Clinton; Yanchun Liu; Lin Chen; Jiatai Xiong; Jian Wang; Weijian Jiang; Qingqian Ma; Angang Ming; et al. (Ecology Letters, 2026)
Although soil respiration is known to increase with warming, the long‐term stability of total forest soil organic carbon (SOC) stocks and their compositional changes remain uncertain. Through a 12‐year soil warming experiment (+1.21°C) in temperate and subtropical forests, we found that SOC content remained stable in both 0–10 cm and 10–20 cm layers. A supporting global meta‐analysis further indicated that substantial SOC loss in forests occurs only under sustained warming exceeding 2°C. However, after 12 years, warming induced distinct compositional shifts. In the temperate forest, mineral‐associated C and the aromatic C/O‐alkyl C ratio declined, suggesting weakened mineral protection and lignin decomposition. Conversely, in the subtropical forest, alkyl C and the alkyl C/O‐alkyl C ratio increased, indicating accumulation of recalcitrant compounds. These results demonstrate that while mild long‐term warming below 2°C can maintain overall SOC stocks, it drives ecosystem‐specific compositional transformations that may influence future soil C persistence under continued climate change.

Combined Microplastics and Cadmium Exposure Induces Persistent Gut Microbiota Dysbiosis in Pearl Oyster Pinctada fucata martensii - Luomin Huang; Yujing Lin; Lintao Liu; Qin Su; Jiaen Liu; Chuangye Yang; Jiaying Yao; Zixin Gao; Yuewen Deng (Fishes, 2026)
In marine aquaculture environments, microplastics (MPs) and cadmium (Cd) are widespread contaminants that may jointly affect host–microbe interactions. Here, we examined the combined effects of MPs (5 mg/L) and Cd (5 μg/L) on the intestinal microbial community of pearl oysters after a 48 h exposure, followed by a 5-day recovery period. Gut microbiota dynamics were characterized using 16S rRNA gene sequencing. Alpha diversity did not vary significantly, whereas beta diversity showed marked alterations in community composition among the different exposure treatments. LEfSe analysis revealed distinct microbial biomarkers and putative pathogens under each treatment: Sulfitobacter in the MPs-alone group; Vibrio and Candidatus_Megaira in the Cd-alone group; and Tenacibaculum, Roseibacillus, and Enterovibrio across different co-exposure and recovery groups. A brief recovery period partially decreased the abundance of certain pathogens (e.g., Vibrio), yet some taxa (e.g., Enterovibrio and Tenacibaculum) remained enriched. These results indicate that exposure to MPs and Cd, whether alone or in combination, disrupts gut microbial homeostasis in pearl oysters by reshaping community structure and promoting the proliferation of potential pathogens, with some disturbances persisting after exposure ceases. Generally, our findings will aid evaluation of the ecological risks of combined pollutants in marine aquaculture systems.

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Efficient CO2-to-CO conversion in a bubble-plate electrolyzer via catalyst layer thickness control - Qing Hu; Linjie Chao; Yujing Liu; Lin Luo; Zhenmin Cheng (Chemical Engineering Journal, 2025)

Modification effect of prenatal polyunsaturated fatty acids on the associations between air particulate matter exposure and infant's growth: A birth cohort study - Yu Liu; Xiaonan Gu; Lili Qin; Xuanqing He; Minyan Lan; Yujing Chen; Qian Chen; Zhen Wang; Zhaoyan Liu; Lizi Lin; Jing Wei; Yanhong Wei; et al. (Environmental Pollution, 2025)

Multi-target-responsive AIE material for in situ visualization of level 3 features in latent fingerprints - Guoxin Zhuang; Jinxin Wei; Yonglin Wen; Yujing Li; Youpeng Xu; Yisheng Jiang; Xianghui Lai; Liang Meng; Zhiyu Liang; Xiaohui Lin; Lijun Ma; Guosong Lin; et al. (Analytica Chimica Acta, 2025)

Chlorination-properties-performance of polyamide nanofiltration membranes for the rejection of emerging contaminants - Wenhao Su; Wenyu Liu; Haowen Wu; Muhammad Saboor Siddique; Ying Mei; Yujing Qiu; Lin Lin; Hao Guo; Chuyang Y. Tang (Water Research, 2025)

Knockout of SlCBF1 enhances tomato fruit resistance against Botrytis cinerea after chilling stress treatment - Lanting Xiang; Yujing Li; Pan Shu; Jiping Sheng; Lin Shen (Postharvest Biology and Technology, 2025)

Phylogenetic and toxicogenomic profiling of CYPomes to elucidate convergent and divergent insecticide resistance profiles in three rice planthopper species - Kai Lin; Hongxin Wu; Zhongsheng Li; Zichun Zhong; Liuyan He; Yujing Guo; Jie Zhang; Xiaoxia Xu; Wenqing Zhang; Fengliang Jin; Rui Pang (Journal of Pest Science, 2025)

Quantification and comparison of prediction uncertainty associated with different practices of crop modeling - Yujing Gao; Daniel Wallach; Baojing Gu; Liang Tang; Tao Lin; Xini Chang; Toshi Hasegawa; Senthold Asseng; Tamer Kahveci; Gerrit Hoogenboom (Agricultural and Forest Meteorology, 2025)

Nb-modified ZSM-48 as efficient catalysts for hexadecane hydroisomerization - Pengju Wei; Wei Wang; Yujing Chen; Mingming Zhang; Xuerong Zhou; Xiaozhen Chen; Qingquan Lin; Kaixuan Yang; Miao Zhang (Fuel, 2025)

Retearing of type B blind cystic aortic dissection: computational fluid dynamics analysis - Hongbing Chen; Yujing Huang; Tong Su; Qi Wang; Minzhu Zhao; Shangyu Zhang; Ruijiao Lin; Jianbo Li (Physical and Engineering Sciences in Medicine, 2025)

The Combined Effects of Cadmium and Microplastic Mixtures on the Digestion, Energy Metabolism, Oxidative Stress Regulation, Immune Function, and Metabolomes in the Pearl Oyster (Pinctada fucata martensii) - Jiaying Yao; Zixin Gao; Zhixiang Wang; Zhanbo Ge; Yujing Lin; Luomin Huang; Jiaen Liu; Heqi Zou; Chuangye Yang; Robert Mkuye; Yuewen Deng (Fishes, 2025)
The accumulation of cadmium (Cd) and microplastics (MPs) can have major deleterious effects on the health of marine ecosystems and organisms, including the pearl oyster Pinctada fucata martensii. Here, we characterized the effects of Cd and MPs on key biochemical parameters of P. f. martensii via an experiment with various treatments. Pearl oysters were exposed to either only Cd (5 or 50 μg/L), only MPs (5 mg/L), or both Cd and MPs for 2 d, and this was followed by a 5-day recovery period. Measurements of the activities of lipase, amylase, protease, T-ATPase, catalase, glutathione peroxidase, acid phosphatase, and alkaline phosphatase enzymes, as well as the malondialdehyde content in the hepatopancreas, were made at various time points during the experiment. Metabolomics analysis of the gills was also performed. Significant interactions between time and treatment on lipase, protease, and catalase activities were observed. However, no significant effect of time–treatment interactions on amylase and T-ATPase activities was observed. Enzyme activities varied among groups both during the exposure period (6 to 48 h) and the recovery period. The malondialdehyde content was also increased throughout the experiment. Pathway analysis indicated that the purine metabolism, glycerophospholipid metabolism, nucleotide metabolism, arachidonic acid metabolism, neuroactive ligand–receptor interaction, and linoleic acid metabolism pathways were the most commonly affected under different treatments. The findings of our study revealed the differential effects of exposure time and treatment on enzyme activities and metabolites and their respective pathways. Our findings enhance our understanding of the biochemical responses of the pearl oyster P. f. martensii to environmental stressors, particularly Cd and MPs.

Association of early life co-exposure to ambient PM2.5 and O3 with the offspring's growth within two years of age: A birth cohort study - Yu Liu; Kunying Li; Yuchuan Deng; Mengfan Li; Xiaonan Gu; Yujing Chen; Zhaoyan Liu; Lizi Lin; Li Cai (International Journal of Hygiene and Environmental Health, 2025)

Soil respiration related to the molecular composition of soil organic matter in subtropical and temperate forests under soil warming - Yanchun Liu; Hui Wang; Andreas Schindlbacher; Shirong Liu; Yujing Yang; Huimin Tian; Lin Chen; Angang Ming; Jian Wang; Jiachen Li; Zuwei Tian (Soil Biology and Biochemistry, 2025)

Strengthening effect of the CFRP method on fire-damaged segments - Hongbin Chen; Yujing Jiang; Diyang Chen; Xuepeng Zhang; Peng Yan; Bin Wang; Qiwei Lin (Tunnelling and Underground Space Technology, 2024)

High-throughput prediction of stalk cellulose and hemicellulose content in maize using machine learning and Fourier transform infrared spectroscopy - Fanghui Chen; Xing Liu; Chengchen Lu; Mingxiu Ruan; Yujing Wen; Shaodong Wang; Youhong Song; Lin Li; Liang Zhou; Haiyang Jiang; Leiming Wu (Bioresource Technology, 2024)

Highly-efficient peroxymonosulfate activation by porous nano-MgO for tetracycline degradation: Surface hydroxyl groups and oxygen vacancies synergetic mediated nonradical process - Hongmin Zhang; Xudong Wang; Yujing Lin; Yongtao Lv; Licheng Chen; Lei Wang (Process Safety and Environmental Protection, 2024)

Catalytic performance of Cs-V-based non-noble soot oxidation catalyst used for DPF and its enhancement by cerium addition - Yunhua Zhang; Yujing Zhang; Diming Lou; Piqiang Tan; Zhiyuan Hu; Liang Fang; Yi Lin (Journal of Environmental Chemical Engineering, 2024)

An optimal calibration method for MODIS precipitable water vapor using GNSS observations - Yingying Wang; Fei Yang; Peixian Li; Xu Gong; Mengfan Liu; Tairan Xu; Xinbo Lin; Yujing Wang (Atmospheric Research, 2024)

Ursolic acid suppresses fatty liver-associated hepatocellular carcinoma by regulating lipid metabolism - Mingyan Dong; Qi Cui; Yunong Li; Yujing Li; Qiuyu Chang; Ruixue Bai; Minjiie Wei; Lin zhao; Qili Chen (Food Bioscience, 2024)

Particle filter performance of soot-loaded diesel particulate filter and the effect of its regeneration on the particle number and size distribution - Yunhua Zhang; Yujing Zhang; Yi Lin; Liang Fang; Diming Lou (Journal of Cleaner Production, 2024)

Effects of titanium dioxide nanoparticle exposure on the gut microbiota of pearl oyster (Pinctada fucata martensii) - Fengfeng Li; Yujing Lin; Chuangye Yang; Yilong Yan; Ruijuan Hao; Robert Mkuye; Yuewen Deng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Candidate gene mining of GA-mediated regulation of pear fruit shape - Zeyu Xue; Ru Yang; Yadong Wang; Yuchen Ma; Yujing Lin; Zhengao Li; Yuqin Song; Xinxin Feng; Liulin Li (Horticulture, Environment, and Biotechnology, 2024)

Inhibitory effect of malonic acid on Microcystis aeruginosa: Cell morphology, oxidative stress and gene expression - Chunyang Tao; Xiaojun Niu; Dongqing Zhang; Yuejin Liu; Lingling Zhou; Yunhao Han; Yujing Mo; Kaixin Wu; Yu Lin; Zhang Lin (Algal Research, 2024)

Abnormal brain functional network dynamics in amyotrophic lateral sclerosis patients with depression - Sujuan Sun; Yujing Chen; Bing Zhao; Jun Zhu; Tianrui Wen; Bingnan Peng; Qingguo Ren; Xiaohan Sun; Pengfei Lin; Dong Zhang; Shuangwu Liu (Brain Imaging and Behavior, 2024)

Enhanced peroxymonosulfate activation via MOF-derived bimetal core-shell Co-Fe@NC hybrids to degrade emerging pollutants - Hui Li; Xinlei Ren; Wenxue Pan; Shiting Zhu; Jin Zhang; Zhiyuan Yang; Liu Qian; Yueying Wang; Yujing Huang; Lin Guo; Minghui Xiang (Journal of Environmental Chemical Engineering, 2024)

Polymeric microenvironment enhancing polarity response sensitivity for discriminating lipid droplets in cancer cells - Yujing Zuo; Zhiming Gou; Weiying Lin (Analytica Chimica Acta, 2024)

Responses of submerged macrophytes to different particle size microplastics and tetracycline co-pollutants at the community and population level - Hongzhi Mao; Hui Yang; Zhiyan Xu; Qiutong Peng; Shiwen Yang; Lin Zhu; Yujing Yang; Zhongqiang Li (Journal of Hazardous Materials, 2024)

Genome-wide DNA methylation of lesional and peri-lesional skin in vitiligo: a comparative and integrated analysis of multi-omics in Chinese population - Lin Liu; Yuzhou Xue; Yuxin Li; Yangmei Chen; Xingyu Pan; Yujing Huang; Tingqiao Chen; Judan Zhong; Xinyi Shao; Yihuan Pu; Jin Chen (Human Genetics, 2024)

A dual fragment triggered DNA ladder nanostructure based on logic gate and dispersion-to-localization catalytic hairpin assembly for efficient fluorescence assay of SARS-CoV-2 and H1N1 - Chen Zhou; Yujing Chuai; Chiliang Lin; Dongsheng Wang; Qiuju Wang; Haimin Zou (Analytica Chimica Acta, 2023)

MicroRNA-650 Regulates the Pathogenesis of Alzheimer’s Disease Through Targeting Cyclin-Dependent Kinase 5 - Li Lin; Xiaodong Liu; Xuejun Cheng; Yujing Li; Marla Gearing; Allan Levey; Xiaoli Huang; Ying Li; Peng Jin; Xuekun Li (Molecular Neurobiology, 2023)
Alzheimer’s disease (AD) pathogenesis feature progressive neurodegeneration, amyloid-β plaque formation, and neurofibrillary tangles. Ample evidence has indicated the involvement of epigenetic pathways in AD pathogenesis. Here, we show that the expression of microRNA 650 (miR-650) is altered in brains from AD patients. Furthermore, we found that the processing of primary miR-650 to mature miR-650 is misregulated. Bioinformatic analysis predicted that miR-650 targets the expression of three AD-associated components: Apolipoprotein E (APOE), Presenilin 1 (PSEN1), and Cyclin-Dependent Kinase 5 (CDK5), and we have experimentally confirmed that miR-650 is able to significantly reduce the expression of APOE, PSEN1, and CDK5 in vitro. Importantly, the overexpression of miR-650 was further shown to significantly alter the CDK5 level and ameliorate AD pathologies in APP-PSEN1 transgenic mice. Overall, our results indicate that miR-650 influences AD pathogenesis through regulation of CDK5.

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Gelsemine, a natural alkaloid extracted from Gelsemium elegans Benth. alleviates neuroinflammation and cognitive impairments in Aβ oligomer-treated mice - Liping Chen; Hanbo Pan; Yujing Bai; Huiqin Li; Wen Yang; Zhi-Xiu Lin; Wei Cui; Yan-Fang Xian (Psychopharmacology, 2020)

Using Orthogonal Combined Signals in Broadband ADCP for Improving Velocity Measurement - Yujing Lin; Fei Yuan; En Cheng (Journal of Marine Science and Engineering, 2020)
Broadband Acoustic Doppler Current Profiler (BBADCP) is a widely used technology in velocity measurements. To adapt to the varied water environment and different measurement requirements, flexible tuning of transmitted signal parameters will improve the feasibility and accuracy of velocity measurement. Compared with the conventional signal, the orthogonal combined signal designed in this paper can generate a wealth of signal combination examples and improve the accuracy of the velocity measurement under the same conditions. The proposed orthogonal combined signal consists of two orthogonal sub-signals with a symmetrical spectrum. Each is designed based on time delay to eliminate or weaken the current velocity ambiguity. Then, the processing method of the received signal when the pulse signals are the same or different coded signal is discussed. The numerical simulation results show that, when using the proposed method, the standard deviation of the estimated current velocity has different degrees of reduction at different current velocities. Our simulation also shows that, compared to the convention method, the proposed method can improve the SNR by 10 dB. This can help significantly increase the scope of the configuration.

Characterization of a Saccharum spontaneum with a basic chromosome number of x = 10 provides new insights on genome evolution in genus Saccharum - Zhuang Meng; Jinlei Han; Yujing Lin; Yiyong Zhao; Qingfang Lin; Xiaokai Ma; Jianping Wang; Muqing Zhang; Liangsheng Zhang; Qinghui Yang; Kai Wang (Theoretical and Applied Genetics, 2020)

A new triterpene diglycoside from the roots of Bupleurum chinense DC. and its inhibitory effect on adipogensis in 3T3-L1 cells - Yujing Feng; Zhou-Wei Wu; Yanyan Luo; Liang Chen; Yufeng Cao; Lun Wang; Aftab Yaseen; Bin Chen; Ashfaq Ahmad Khan; Ming-Kui Wang; Guo-Lin Zhang; Xin-Feng Wang; et al. (Medicinal Chemistry Research, 2019)

Identification of significant single nucleotide polymorphisms for resistance to maize rough dwarf disease in elite maize (Zea mays L.) inbred lines - Derong Hao; Yujing Cheng; Guoqing Chen; Huhua Lu; Mingliang Shi; Zhenliang Zhang; Xiaolan Huang; Yuxiang Mao; Lin Xue (Euphytica, 2015)